Resumption of postpartum ovarian activity in goats as affected by kidding season and body condition score under Egyptian conditions - ABSY, G; ABUZEAD, S M M; ZEIDAN, A E (The Indian Journal of Animal Sciences, 2014)
Female Baladi goats (45) were used to study the effects of kidding season and body condition score (BCS) on the resumption of postpartum ovarian activity. Out of 45 does, 12, 11, 10 and 12 were kidding during winter, spring summer and autumn respectively. Does within each season were allocated into 2 categories, those having low and medium BCS. Postpartum ovarian activity was monitored by measuring progesterone concentration in the sera samples that were collected twice weekly starting from day 14 up to week 8 postpartum. The results revealed that the percentages of does ovulated Within 8 weeks postpartum were 41.67, 54.55, 70 and 83.33% for animals that were kidding during winter, spring, summer and autumn respectively. Percentages of the resumption of ovarian activity of the does kidding during summer or autumn were sigmficantly (P<0.01) higher than that kidding during winter or spring. Percentages of the resumption of ovarian activity in does with low and medium BCS were 50 and 73.90% respectively. The average interval from kidding to first postpartum ovulation in does of kidding season and BCS on the incidence of silent heat accompanying the first postpartum ovulation were 60 00, 66.67, 71.43 and 50% in does parturated during winter, spring, summer and autumn respectively. However, the effect of kidding season on progesterone concentration in the postpartum does was not significant.